The Effect of Work Family Conflict, Teamwork and Job Satisfaction on Employee Performance at Basarnas Office Kendari - Usman, Usman; Takdir Syaifuddin, Dedy; Nasrul, Nasrul (International Journal of Management and Education in Human Development, 2021)
The purpose of this study is to examine and explain the effects of simultaneous among Work Family Conflict, Teamwork, and job satisfaction of the Performance Officer Office of Kendari Basarnas. To examine and explain the effect of Work Family Conflict on the Performance of Kendari Basarnas Office Employees. Test and explain the effect Teamwork on the Performance of Kendari Basarnas Office Employees. To examine and explain the effect of Job Satisfaction on the Performance of Kendari Basarnas Office Employees. The population in the study are all the employees of the Agency Sar National Kendari, which overall is an employee of domestic civil (PNS), which amounted to as much as 114 Employees. Measurement of data in this study using a Likert scale. Mechanical analysis of the data used in the study is that the analysis of the data statistics descriptive and statistical inferential namely analysis regression linear multiple by using software SPSS version 20. Based on the results of the analysis of the data, the results showed that Work Family Conflict, Teamwork and Job Satisfaction effect positive manner together against the performance of employees. This means that the increase in Work Family Conflict, cooperation Team and Job Satisfaction is simultaneously have positively contributed to the improvement of the performance of employees. Work Family Conflict has a positive effect on employee performance. This means that the increase in the Work Family Conflict of employees is described as having a positive contribution to improving employee performance. Teamwork has a positive effect on employee performance. That is an increase Teamwork employee has a contribution that is significant to the performance of an employee. Job satisfaction has a positive effect on employee performance. Meaning Satisfaction Work that either give contributions that positively on the improvement of the performance of employees.